Gambaran Pengetahuan Terapi Akupresur pada Pasien Diabetes Mellitus - Ni Made Sri Regiantari; I Gusti Ketut Gede Ngurah (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2022)
Acupressure therapy is a traditional therapy that uses hands or blunt objects to massage. Diabetes Mellitus is a disease that correlates with blood sugar levels exceeding normal limits. This study aims to determine the description of acupressure therapy in Diabetes Mellitus in Pedungan Village, South Denpasar District, Denpasar City 2021. The population of this study was 50 respondents and a sample of 44 respondents, with a descriptive type of research used a sampling technique, namely purposive sampling. The measuring instrument used was a questionnaire knowledge of acupressure therapy. The results of this study indicate that of the 44 respondents, the majority were 40-49 years old as many as 20 respondents (45.5%). There were 24 female respondents (54.5%). The final high school education level were 28 respondents (63.6%). work as private employees 19 respondents (43.2) The conclusions of this study were 18 respondents with less knowledge (40.9%), 14 respondents with sufficient knowledge (31.8%), and 12 respondents with good knowledge (27.3%), lack of knowledge because they are not exposed to information. Advice on knowledge related to Diabetes Mellitus and Acupressure therapy with poster.